Intimate partner violence - Hattery, Angela (Rowman & Littlefield Publishers, 2009)
Until recently, domestic violence, as it has been referred to, was a problem to be dealt with inside the family. In this ground-breaking work, Hattery's unique approach provides a detailed theoretical discussion of race, class, and gender-effects on intimate partner violence and a thoughtful discussion of the interactions of these factors.